Analysis Of Mobility Pattern And Challenges Of Transportation Needs Of The Elderly In A Fast Growing City In Nigeria - Oyesiku, Kayode. O (Advances in Social Sciences Research Journal, 2016)
Unprecedented growth of ageing population may not be of concern as much as unpreparedness of developing countries to recognized the phenomenon and provides for the mobility needs to sustain them. In Nigerian, about 8% of the population are over 65 years and expected to increase 14% next ten years, arising from increase in longevity and declining birth rates, thus increasing challenges of demands on country’s transportation systems. Elderly gradual alienation from use of public transport leads researchers to getting more concern about challenges of their mobility. Understanding the pattern of elderly mobility may assist transport planners in providing for their mobility. This paper focuses on pattern elderly mobility in a developing country, using a fast growing city as case study and identifies most important determinant of satisfaction level of elderly use of existing transport services. The study is part of travel survey of a fast growing city in Nigeria, using structured questionnaire as survey instrument. 556 questionnaires administered on 65 years old and over were completed out of 720 respondents were excised for analysis presented in this paper. The main findings show that the frequent mode are by taxi and commercial motorcycles; the latter not only more expensive but also uncomfortable, very unsafe though ubiquitous, readily available and accessible. The multiple regression analysis employed quantitatively ascertained that inconveniences of use of public transportation is the most important determinant of factors influencing level of satisfaction in use of transport services provided. The study notes urban land use planning must integrate functional public transport system towards addressing mobility crisis of the elderly and social system must support elderly to financially cope with increasing cost of transportation with a view to restoring their long loss social independence and brings them to fore front of the realization of their mobility needs.